Seafood safety and consumption in coastal Bangladesh: unpacking knowledge, attitudes, preferences, and environmental concerns - Nitai Roy; Sultan Mahmud Imran; Aysha Siddiky; Samia Sultana; Sumana Mahmud; Abdullah Al Adib; Kamal Krishna Biswas (Journal of Nutritional Science)
The objective of this study was to explore the knowledge and attitudes regarding seafood safety and consumption, along with preferences and environmental issues in coastal Bangladesh. A cross-sectional, consumer-based survey was conducted in Bangladesh from September to November 2023, targeting 1100 participants aged 18 years and older across seven coastal districts. Convenience sampling and in-person interviews were used for the data collection. The average knowledge and attitude scores toward seafood safety and consumption were 48.2% and 63.5%, respectively. Several factors influenced seafood safety and consumption knowledge, including age, education level, family size, religion, and residence in coastal areas (all P < 0.05). In contrast, attitudes toward seafood safety and consumption were shaped by education level, family size, employment status, seafood allergies, and history of seafood poisoning (all P < 0.05). The most commonly consumed seafood was rupchanda, followed by shrimp. Most participants consumed seafood for its health benefits, with no significant seasonal impact on seafood consumption. Overfishing and climate change were recognised as the most alarming environmental dangers identified by the participants. Coastal communities in Bangladesh have demonstrated moderate attitudes, but relatively low knowledge of seafood safety and consumption. Targeted educational programmes, including community workshops on safe handling and storage, school-based programmes on marine conservation, and digital campaigns via SMS/social media, are needed to improve seafood safety knowledge, while promoting sustainable consumption practices is crucial for addressing environmental concerns like overfishing. Additionally, improving market accessibility and highlighting the health advantages of seafood can drive more informed and healthier consumption choices.